2000
DOI: 10.1074/jbc.275.19.14388
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-activated Receptor-γ Pathway Inhibits Osteoclast Differentiation

Abstract: The nuclear receptor and transcription factor, peroxisome proliferator-activated receptor-␥ (PPAR-␥), regulates the activity of other transcription factors in the adipogenic differentiation and inflammatory response pathways. We examined the possible function of the PPAR-␥ pathway in osteoclast (Ocl) formation from CD34؉ hematopoietic stem cells (CD34 ؉ HSCs), using a co-culture system comprised of human mesenchymal stem cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 36 publications
(47 reference statements)
7
74
0
4
Order By: Relevance
“…There exists a major discrepancy regarding the role of PPARg in osteoclastogenesis. Previous in vitro studies showed that PPARg agonists inhibit osteoclastogenesis via NF-kB, (53) NFATc1, (54) or mitogen-activated protein (MAP) kinase pathway (55) in osteoclast precursors. In contrast, osteoclast-specific deletion of PPARg has resulted in osteopetrotic phenotype with compromised RANKL signaling and osteoclast differentiation, indicating that PPARg in fact has a pro-osteoclastic potential.…”
Section: Discussionmentioning
confidence: 99%
“…There exists a major discrepancy regarding the role of PPARg in osteoclastogenesis. Previous in vitro studies showed that PPARg agonists inhibit osteoclastogenesis via NF-kB, (53) NFATc1, (54) or mitogen-activated protein (MAP) kinase pathway (55) in osteoclast precursors. In contrast, osteoclast-specific deletion of PPARg has resulted in osteopetrotic phenotype with compromised RANKL signaling and osteoclast differentiation, indicating that PPARg in fact has a pro-osteoclastic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Mbalaviele et al (2000) showed that the activation of PPAR-γ pathway by an endogenous PPAR-γ ligand, blocked the effects of OPG ligand and thus, inhibited the formation and activity of osteoclasts in human mesenchymal stem cells through the inhibition of receptor-activated NF-κB ligand (RANKL) blocking the NF-κB pathway. Okazaki et al (1999) similarly reported that the thiazolidindione treatment decreased the number of osteoclast-like cells induced by 1,25-(OH)2D3 or PTH, suggesting the inhibitory role of PPAR-γ activation on bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent work by Chan et al (2007) demonstrated that PPAR-γ agonist added to human peripheral blood mononuclear cells culture resulted in significant dose-dependent inhibition of multinucleated osteoclast formation. Although the precise mechanisms regarding the association of PPAR-γ and osteoclastogenesis are not clarified, the antagonistic effects of PPAR-γ on the transcription factor NF-κB, which is the fundamental pathway for RANKL signaling and essential for osteoclast development, survival and function, and the subsequent association of osteoprotegerin, a critical inhibitory factor in osteoclastogenesis, are suggested (Mbalaviele et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxisome proliferator-activated receptor (PPAR)-γ belongs to the nuclear hormone receptor family, which is predominantly expressed in the adipose tissue, and also plays an important role in the bone micro environment (6). In addition, PPAR-γ activation seems to have regulatory effects on bone metabolism through regulating their differentiation or activation into osteoclasts (7)(8)(9). However, evidence on whether the activation of PPAR-γ may affect bone metabolism through the activation or inhibition or cell lineages is not enough for conclusion.…”
Section: Introductionmentioning
confidence: 99%